Green logistics application to reduce operating costs for Vietnam logistics enterprises - Huynh Dang Khoa (Business & IT, 2020)
Green logistics is one of the current trends that logistics enterprises in countries have been applying for their logistics activities to achieve economic efficiency issues, but still ensure environmental friendliness and achieve social responsibility. In this article, the author wants to introduce readers the trend of green logistics applications in reducing operating costs of logistics enterprises; illustrated by typical successful situations of businesses around the world. Since then, propose some recommendations for Vietnam logistics enterprises in applying green logistics into enterprises to have the opportunity to reduce operating costs, integrate well with the world, and create competitive advantage for businesses in the same industry.